Impact of postoperative weight gain on complications after liver surgery. Issue 5 (May 2020) - Labgaa, Ismail; Joliat, Gaëtan-Romain; Grass, Fabian; Jarrar, Ghada; Halkic, Nermin; Demartines, Nicolas; Hübner, Martin
Abstract: Background: Recent data has suggested that excessive perioperative weight gain may be associated with adverse outcomes after abdominal surgery, but this observation remains unexplored following liver surgery. The present study aimed to investigate the predictive value of perioperative weight fluctuation in predicting complications after liver surgery. Methods: Retrospective monocentric analysis of consecutive patients undergoing liver surgery between 2010 and 2016. Patients without available perioperative weight were excluded. Test variable was postoperative weight change (ΔWeight) measured on day 2 (POD2). Primary outcome was postoperative major morbidity according to Clavien classification (grades III–IV). Secondary outcomes were overall complications, Comprehensive Complication Index (CCI) and length of hospital stay (LoS). Area under the receiver operating characteristic curve (AUROC) and logistic regression with multivariable analysis were performed. Results: A total of 181 patients met the inclusion criteria. Major and overall postoperative complications were reported in 25 (14%) and 87 (48%) patients, respectively. On POD2, median ΔWeight was 2.6 Kg (IQR: 1.1–4.0). Patients with major complications showed increased ΔWeight of 4.2 Kg (IQR: 2.7–5.7), compared to 2.3 Kg (IQR: 0.9–3.7) in patients without major complications (p < 0.001). AUROC of ΔWeight for major complications was 0.74, determining an optimal cut-off of 3.5 Kg, which yielded a negative predictive value of 94%. Multivariable analysis identified ΔWeight ≥3.5 Kg as independent predictor of major complications (OR, 4.73; 95% CI, 1.51–14.80; p = 0.008). Conclusion: ΔWeight ≥3.5 Kg was independently associated with major complications after liver surgery. Perioperative fluctuation of weight appears as an important predictor of adverse outcomes after liver surgery.